Exposure to Inorganic Mercury Causes Oxidative Stress, Cell Death, and Functional Deficits in the Motor Cortex - Teixeira, Francisco B.; de Oliveira, Ana C. A.; Leão, Luana K. R.; Fagundes, Nathália C. F.; Fernandes, Rafael M.; Fernandes, Luanna M. P.; da Silva, Márcia C. F.; Amado, Lilian L.; Sagica, Fernanda E. S.; de Oliveira, Edivaldo H. C.; Crespo-Lopez, Maria E.; Maia, Cristiane S. F.; et al. (Frontiers in Molecular Neuroscience, 2018)
Mercury is a toxic metal that can be found in the environment in three different forms – elemental, organic and inorganic. Inorganic mercury has a lower liposolubility, which results in a lower organism absorption and reduced passage through the blood–brain barrier. For this reason, exposure models that use inorganic mercury in rats in order to evaluate its effects on the central nervous system are rare, especially in adult subjects. This study investigated if a chronic exposure to low doses of mercury chloride (HgCl2), an inorganic form of mercury, is capable of promoting motor alterations and neurodegenerative in the motor cortex of adult rats. Forty animals were exposed to a dose of 0.375 mg/kg/day, for 45 days. They were then submitted to motor evaluation and euthanized to collect the motor cortex. Measurement of mercury deposited in the brain parenchyma, evaluation of oxidative balance, quantification of cellular cytotoxicity and apoptosis and density of mature neurons and astrocytes of the motor cortex were performed. It was observed that chronic exposure to inorganic mercury caused a decrease in balance and fine motor coordination, formation of mercury deposits and oxidative stress verified by the increase of lipoperoxidation and nitrite concentration and a decrease of the total antioxidant capacity. In addition, we found that this model of exposure to inorganic mercury caused cell death by cytotoxicity and induction of apoptosis with a decreased number of neurons and astrocytes in the motor cortex. Our results provide evidence that exposure to inorganic mercury in low doses, even in spite of its poor ability to cross biological barriers, is still capable of inducing motor deficits, cell death by cytotoxicity and apoptosis, and oxidative stress in the motor cortex of adult rats.